THE ROLE OF FINANCIAL PERFORMANCE OF LOCAL GOVERNMENTS IN MODERATING THE FUNDS IN THE EDUCATION AND HEALTH SECTORS ON THE HUMAN DEVELOPMENT AND COMMUNITY WELFARE INDEX - Naomi Nathania Wijaya; Faisol, Hestin Sri Widiawati (Adisam Publisher, 2024)
This research is motivated by the fact that there is still an inequality in the level of Human Development and Community Welfare Index in Regencies/Cities in East Java. The Human Development and Community Welfare Index (HDWI) is one of the government's objectives for managing its regions. The purpose of this study is to analyze the ability of the Financial Performance of Local Governments to become a mediator for the allocation of funds in the education and health sectors to the HDWI. This study uses a quantitative method with panel data regression analysis through the Random Effect Model approach as the result of selecting the best model. The sample used in this study includes 38 regencies/cities located in East Java. The results obtained in this study are (1) the allocation of funds in the education sector directly affects the HDWI. (2) the allocation of funds in the health sector does not directly affect the HDWI. (3) The role of local government financial performance plays a significant role in moderating the influence of education funding on the HDWI, although it has a negative coefficient. Then, local government financial performance has not been able to moderate health funding in influencing the HDWI. (4) The Financial Performance of the Regional Government has not been able to moderated the Health Fund in influencing the HDWI.